Inferior frontal gyrus white matter abnormalities in obsessive-compulsive disorder - Gonçalves, Óscar F. (2015)
The aim of the present study is to explore obsessive-compulsive disorder (OCD)-related abnormalities in white matter connectivity in OCD for a core region associated with inhibitory control [i.e. inferior frontal gyrus (IFG)]. Fifteen patients with OCD (11 men) and 15 healthy controls (nine men) underwent diffusion tensor imaging scanning to study four diffusivity indexes of white matter integrity [fractional anisotropy, mean diffusivity (MD), axial diffusivity and radial diffusivity (RD)]. The results showed that persons with OCD manifested significantly lower fractional anisotropy levels in the bilateral IFG as well as its parcellations in the pars opercularis, pars triangularis, and pars orbitalis. Significantly higher levels of MD, RD were evident for the OCD group in the IFG as a whole as well as in the bilateral subregions of the pars triangularis and pars opercularis (for MD and RD), the right side of the pars orbitalis (for RD), and the left side of the pars triangularis and right side pars opercularis (for axial diffusivity). Overall, the results suggest significant alterations in structural connectivity, probably associated with myelination and axonal abnormalities in the IFG of OCD patients.